1996
DOI: 10.1016/s0022-3913(96)90299-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results with immediate overdentures: An evaluation of 4.5 years

Abstract: Please be advised that this information was generated on 2018-05-12 and may be subject to change.T reatm en t r e su lts w ith im m ed iate ov erd en tu res: An ev a lu a tio n o f 4.5 y ea rs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Deteriorating muscle strength and coordination in elderly patients may lead to problems fabricating complete dentures, as well as difficulty achieving and maintaining acceptable denture stability and retention 5‐7 . Moreover, elderly patients often have difficulty adapting to new complete dentures and have problems attaining comfortable and efficient denture function 4,8,9 …”
mentioning
confidence: 99%
“…Deteriorating muscle strength and coordination in elderly patients may lead to problems fabricating complete dentures, as well as difficulty achieving and maintaining acceptable denture stability and retention 5‐7 . Moreover, elderly patients often have difficulty adapting to new complete dentures and have problems attaining comfortable and efficient denture function 4,8,9 …”
mentioning
confidence: 99%
“…Initially restricted to maxillofacial indications, including craniofacial deficiencies and epithetics, 12–14 the use of magnetic attachments has been successfully established for implant‐retained removable dental prostheses. Clinical and in vitro studies confirmed the advantages of magnetic attachments for these indications 11,15–22 Advantages include control of load transmitted to implants, and the relative ease of prosthesis fabrication in complicated patients.…”
mentioning
confidence: 86%
“…Since the 1960s, an analysis of several longitudinal studies [4][5][6][7][8][9] showed benefits to overdentures, such as the retardation of progressive residual ridge reduction, 4,5 better stability of the dentures, as well as better load transmission of the prostheses, especially of mandibular overdentures, allowing improved masticatory ability and efficiency. [6][7][8][9][10][11][12] There have also been reports of psychological benefits to patients because they do not feel they are edentulous. 7 This may be an important factor in maintaining a more positive self-image.…”
mentioning
confidence: 99%